Social agglomeration externalities - Rainald Borck (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
This paper examines social agglomeration externalities. Using survey data from the German Socio-Economic Panel, I examine the link between city size and different measures of consumption, social interaction and social capital. Further, using responses to satisfaction questions, I analyse whether individuals are compensated for diseconomies of agglomeration by positive agglomeration externalities in other areas. This equilibrium hypothesis cannot be rejected.
Keywords: R22; R23; 330; agglomeration; externalities; social interaction